Children’s Well-being and Leisure Through a Participatory Photographic Mapping - Oyarzún Gómez, Denise; Reyes Espejo, María Isabel (Revista de Psicología, 2021)
Well-being refers to a positive state in which personal, relational, and collective needs and aspirations of individuals and communities are satisfied. Its approach to children is an emerging field of research that has been studied mainly from an adult-centred perspective. This research describes, in an exploratory way, the perceptions of well-being associated with the free time of children living in an urban camp in Viña del Mar, Chile. It is a qualitative, descriptive, and transversal study that, from a dialogic work with children, monitors of a popular library and the researchers, analyses the participatory photographic mapping process. The results derived from a thematic analysis show that the well-being of children is territorially linked to the use of free time in recreational, care and leisure activities. The places of recreation in the neighbourhood are the ravine, the park, and the popular library, which are the themes that provided the most novel findings. The implications of this study are that well-being associated with leisure time are important components of the positive development of children who are the protagonists of their lives.